Contribution of DGs in the stability and voltage drop reduction for future MV network in desert regions - Bouafia Abdelkader; Labed Djamel (Institute of Advanced Engineering and Science, 2020)
Day by day, the integration of decentralized generation in medium voltage networks becomes more important during the last years and even in the near future. This increase causes, at the same time, several negative effects and rarely positive impacts on the stability of the network. Therefore, this work aims at analyzing the impact of ambient temperature on radial distribution network parameters’ e.g.: voltage drop and stability voltage level (index). Based on MATLAB program, different analyses of distributed generation (DG) insertion influence’s on voltage drop in the radial distribution feeder, as well as the influence of climatic conditions such as ambient temperature on network parameters. The Integration of Photovoltaic DGs in MV networks can play an important role in reducing the global warming effect (in voltage drop, and voltage stability index) especially in radial distribution feeder. Furthermore, it protects network’s parameters if its location and power are well selected.